Implementación de un sistema de gestión del mantenimiento preventivo a la flota de camiones internacional 4300 de la empresa FL Colombia SAS (2022)
A study focused on the management of preventive maintenance of trucks of the International 4300 series of the company FL Colombia SAS was carried out, through which it was possible to integrate knowledge collected from the technical experience combining them with the manufacturer's recommendations, this practice could update the current maintenance procedures, since there was no organization of equipment failure histories, this led to the creation of new follow-up reports for them. In addition, the increase in the availability of Down equipment is obtained, giving it reliability to the operation as revised in the control application. In this way, techniques such as visual and vibration inspections, oil analysis, among others, continue to be used. One of the most relevant points within the investigation is associated with establishing the appropriate methodology which gave rise to the design and development of a tool that allowed the planning and programming of activities in the management of preventive maintenance; Obtaining as a positive result the fulfillment of the stated objectives and it is concluded with the design associated with innovation and the development of new technological trends. Therefore, the company FL Colombia SAS decides to evaluate itself in the current maintenance system, seeking continuous improvement in it to increase its production and fulfillment of goals.